THE POLICY OF THE RUSSIAN EMPIRE GOVERNMENT IN PROMOTING NATIONAL EDUCATION IN TURKESTAN - Isroilov Zokhidjon Vokhidjon ogli (Journals Park Publishing, 2023)
Undoubtedly, the media has always held a significant place in human society. In any civilized society, it is not possible for any social or political movement to progress without media. In the current era of globalization, it is unimaginable to envision human life without media, without newspapers and magazines, without radio and television. Just as a person cannot live without bread and water, they also cannot live without spiritual nourishment, and living without media is also impossible.
Keywords: Turkestan's people, the rule of Russia, schools, madrasahs, national education, Russian policy, national schools, Russian schools, historical heritage, native population, knowledge, education, people's consciousness, early 20th century, Minister of National Education, teachers, Russian Empire Government, K.P. Kaufman, Turkestan General-Governorship, Russian-language schools, male and female gymnasia, N.O. Rosenbach, Ministry of Education.